Pengaruh Kehilangan dan Berduka terhadap Kondisi Mental Individu - Fina Rismayanti; Sapna Naina Arni Azzani; Nita Anggraeni; Sri Mulyeni (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
Loss and grief are psychological experiences that significantly affect an individual’s mental state. This process involves various emotional, cognitive, and behavioral changes that can affect a person’s well-being in the long term. This study aims to describe the emotional, cognitive, and behavioral affects that arise in individuals after experiencing loss, as well as the factors that strengthen or weaken their responses to the grieving process. The method used in this study is qualitative, with a literature review approach from various relevant clinical psychology and mental health studies. The results indicate that individuals who experience loss are vulnerable to increased emotional stress, anxiety, depression, and significant declines in social functioning. Furthermore, this article highlights that the quality of social support received, the way individuals make meaning of the loss, and the coping mechanisms they choose play a crucial role in determining the level of grief response. These factors can either accelerate or delay the healing process. An unresolved grieving process or one that is handled in an unhealthy manner can develop into more serious psychological disorders, such as Prolonged Grief Disorder (PGD). PGD is a condition characterized by difficulty in accepting the loss, which can persist for months or even years. This article emphasizes that loss is not merely an emotional disturbance but also a complex psychological process. This process requires a deep understanding, strong social support, and appropriate interventions to maintain an individual’s mental health and help them recover more effectively.